Conflict management and leadership development using mediation - Algert, Nance T. (Contemporary issues in conflict management and dialogue., 2021)
"Conflict management is an overlooked area in leadership development. Mediation as an intervention method to use in conflict management can be productive for building leadership capacity and organizational development in higher education. Adults average five conflicts per day and people in titled leadership spend over two-thirds of their time engaged in managing conflict. This workbook offers conflict management strategies, models, and processes to support college and university personnel in recognizing and managing conflicts and how to build skill sets that can enhance effective communication and address conflicts"--